Impact of conservation tillage and agronomic biofortification strategies on soil health and grain quality aspects under soybean–wheat cropping system: Impact of conservation tillage and agronomic biofortification strategies on soil health and grain quality aspects under soybean–wheat cropping system - RAGHAVENDRA MADAR; SARIKA NAMDEV; R K VERMA; A RAMESH; M P SHARMA (Journal of Oilseeds Research, 2023)
A field experiment was initiated in 2018 at ICAR-IISR Indore (MP), to study the effect of crop establishment techniques and agronomic biofortification methods on grain yield, crop and soil quality aspects under long-term conservation agriculture (CA) based soybean-wheat cropping system. The experiment was laid out in split plot design with two crop establishment techniques and eight agronomic biofortification methods. The results revealed that significantly higher grain yield, lowest soil pH, highest available nutrients (DTPA-Zn and DTPA-Fe), increased soil enzyme (Dehydrogenase) of soybean and wheat under conservation tillage. Among different agronomic biofortification methods soil application of Zn+Fe (DTPA-Zn and DTPA-Fe) reported significantly higher grain yield, compared to control. However, seed inoculation of microbial strains MDSR 14 + MDSR 34 reported significantly lowest soil pH, highest soil enzyme. Soybean and wheat grain phytic acid/Zn (<15) and phytic acid/Fe (<10) molar ratio was found significantly lower under conservation tillage and foliar application of Zn+Fe. Thus, in long term, adaptation of conservation tillage along with soil or foliar application of Zn+Fe and seed inoculation of MDSR 14 + MDSR 34 could be prominent options to improve yield, soil and crop quality parameters under CA based soybean-wheat cropping system.